POLA PEMBINAAN JAMAAH MASTURAT DALAM MEMBANGUN RUMAH TANGGA SAKINAH PADA MASYARAKAT ISLAM SUKU TERASING DI DESABOBALO KEC. PALASA KAB. PARIGI MOUTONG - Thalib Thalib (ISTIQRA, 2016)
Development patterns Jamaah Masturat in building household Vegas is one form of guidance to people who refer to the pattern masturat, namely: through charity and charitable intiqali maqami. In this pattern has tersenidiri provisions, such as: charity intiqali; fie sabilillah out for three days, fifteen days, forty days, and two months of India-Pakistan. Likewise maqami charities, such as: istiqamah turned home study groups (plus the halaqah Quran, muzakarah six properties, taskil, and consultation), remembrance wal worship, simple living and educating children Islamically, solemn husband and husband thrust keuar FII sabilillah. It is a reference and will be developed into the elements of coaching by Jamaah masturat doing business coaching, especially in building household sakinah. The elements of this guidance by Jamaah Masturat later developed into a coaching model khuruj fie sabilillah in the form of charity and charitable maqami intiqali. Intiqali maqami charity and is then used as a model of coaching in fostering individual and community in the form of reconciliation itself through out in the way of God and charity in the form of charity maqami, in this way every individual is expected to change its behavior to better. This is the study of this research, especially in the Islamic community isolated tribe in the village Bobalo mountainous region Maganggal and Membusul